Strengthening the Local Women's Forum in Tosari Pasuruan District as an Early Detection of Social Conflict in the Tengger Tribe - Rochmawati, Ida; Azizah, Imroatul; Fathurrohman, Amang (Jurnal Soeropati, 2024)
This study explores the dynamics of social harmony and conflict prevention in the Tengger ethnic community in Tosari Sub-district, Pasuruan Regency, using the Community-Based Research method. The results highlight the crucial role of local women's forums in promoting interfaith harmony, which is reflected in participatory activities and community empowerment efforts. Strategic measures, such as the â€œBhinneka Tunggal Ikaâ€ Village initiative, demonstrated success in strengthening the Forum through collaboration with key organizations. The research identified tangible changes, including stability and harmony in the community, conflict prevention through dialogue and cultural wisdom, and improved education that contributes to local development. The action phase of the research focused on maintaining the active involvement of the local women's forum, strengthening inter-organizational cooperation, developing a holistic conflict prevention strategy, improving communication between religious communities, and establishing a Consultation and Mediation Forum. Continuous monitoring and evaluation ensured the sustainability and effectiveness of the strategies implemented.